Temperamental characteristics in childhood migraine without aura: a multicenter study - Esposito M (Dove Medical Press, 2013)
Maria Esposito,1 Rosa Marotta,2 Beatrice Gallai,3 Lucia Parisi,4 Giuseppina Patriciello,1 Serena Marianna Lavano,2 Giovanni Mazzotta,5 Michele Roccella,4 Marco Carotenuto11Center for Childhood Headache, Clinic of Child and Adolescent Neuropsychiatry, Department of Mental Health, Physical and Preventive Medicine, Second University of Naples, Naples, Italy; 2Department of Psychiatry, "Magna Graecia" University of Catanzaro, Catanzaro, Italy; 3Unit of Child and Adolescent Neuropsychiatry, University of Perugia, Perugia, Italy; 4Child Neuropsychiatry, Department of Psychology, University of Palermo, Palermo, Italy; 5Unit of Child and Adolescent Neuropsychiatry, AUSL Umbria 2, Terni, ItalyBackground: Children with migraine seem to be more anxious, sensitive, deliberate, cautious, fearful, vulnerable to frustration, tidy, and less physically enduring than comparisons. To the best our knowledge no studies about the temperamental and the characterial dimension aspects in childhood migraine was conducted. Therefore, the aim of the present study was to describe the temperamental and character aspects in a sample of children affected by migraine without aura (MoA) and their relationship with clinical aspects of MoA such as frequency, duration, and severity of attacks.Materials and methods: In our study, 486 children affected by MoA (239 male, 247 female) aged 7–12 years, (mean 10.04 ± 2.53 years) and 518 typical developing children comparable for age (P = 0.227) and sex (P = 0.892) were enrolled to assess their temperamental characteristics. The mothers of all subjects filled out the Junior Temperament and Character Inventory: Parent Version.Results: Children affected by migraine show a higher prevalence of harm avoidance and persistence temperamental domains (P < 0.001) and significantly lower prevalence of the self-directedness character trait (P = 0.023) with respect to the comparisons, according to Cloninger's model. The Spearman rank correlation analysis shows a significant relationship between migraine characteristics and temperamental domains.Conclusion: The present study first identified differences in temperamental characteristics in children affected by MoA with respect to the comparisons, suggesting the need for this evaluation in order for better psychological pediatric management of children with migraine, with possible consequences and impact on the future outcomes of these subjects.Keywords: migraine without aura, children, temperament, JTCI